Governance of cities in devolved government in Kenya: experiences from Kisumu. - Onyango, George M.; Agong', Stephen G. (Management Research & Practice, 2018)
Devolution in Kenya has had ramification on local governments especially urban areas. Kisumu City is unique as the only city with a rural county hinterland. It has created a challenge for the County Executive in terms of managing County expectations and City interests in terms of governance. This paper looks at Kisumu in terms of the governance structures, spatial planning and finance as key aspects of having an effective city management and governance. It points out the gaps that exist within the legal framework that operationalizes the devolved structures for the city. It allows for an appreciation of the management and governance structures of the city as it strives to put in place systems that would make devolution for the city to work
Keywords: Devolution; Governance; Cities; Kenya